ANALISIS PEMASARAN KOMODITI PANILI (Studi kasus di Propinsi Sulawesi Utara) - NURASA, TJETEP; SUPRIATNA, ADE (SOCA: Jurnal Sosial Ekonomi Pertanian; Vol. 5, No. 3 November 2005)
This study was conducted in 2002 dan took place in Province of North Sulawesi North. Sub-Province of Minahasa as one of the North Sulawesi center of vanilla production was chosen for location of study. The objectives of study were: (i)to analyze the profitability of vanilla farm, ( ii) to identify the channel of vanilla marketing dan, its margin in each agent of marketing, dan ( iii) to analyze the role of attribute of product quality to vanilla price. Research used method of survey structure. Primary data were collected from 60 farmers, 15 merchants, 5 product processing, dan 2 exporters. While secondary data were collected from Central Agency of Statistics, the Office of Estate Crops, reports of Research Institute, dan others relating to this study. Results showed, that in one cycle of production ( 10 year), vanilla farm required production cost about Rp.86,4 million per hectare consisting of labor fee ( 82,7%), input productions ( 11,4%), dan other costs ( 5,9%). It took a total production of Rp.209,3 million dan a total income of Rp.122,9 million per hectare. Efficiency rate of vanilla farm was enough high. With interest rate 24 dan 30 %, vanilla farm reached B/C Ratio of 3,58 dan 2,45, dan reached NPV of Rp.35,03 million dan Rp.26,07 million, respectively. Value of IRR indicated that vanilla farm would reach break-even point in interest rate of 74,6 percent. The channel of vanilla marketing was still modestly, farmer as vanilla producer at most selling to small (collecting) merchant ( 50%), large merchant ( 40%), dan large merchant/exporter ( 10%). A highest marketing margin was obtained by large merchant/exporter (Rp.7.000/kg), large merchant (Rp.4.495/kg), dan small merchant (Rp.1.885/kg). The price of vanilla was determined by diameter, long, dan color of fruit where long of fruit gave a biggest parameter, namely 0.67. It means that accretion of fruit length equal to 10 percent will improve the vanilla price equal to 6.7 percent. Some suggestions to increasing productivity dan quality of vanilla product were; ( i) knowledge dan skilled of farmer have to be improved continuously in line with the increasing of new innovation, ( ii) role of farmer group have to be improved, dan (iii) private sector as agent of agribusiness like product processing dan exporter have to include in assisting farmer. Their participation were very expected to assist farmer, especially in maintaining vanilla crops, supplying input of production, dan marketing.
Keywords: Vanilla, Farm, Marketing, North Sulawesi.